(untitled) (Global Journals of Research in Engineering, 2022)
This research shows the development of a semantic web model whose objective is to create a knowledge base of traditional groups and music genres of the city of Bogota the method in which the information is transmitted to and from the knowledge base created is through the use of an API based on REST architecture which uses the HTTP protocol this information is presented in a web portal Visitors and users who visit the portal can carry out searches that are based on SPARQL to contact music groups according to a series of filters such as geographical location music genre market background rates among others this project becomes a digital alternative for musical groups in the city of Bogota to promote their services and provide a virtual channel of contact quickly and safely this aims to improve the quality of life of members of musical bands